Synthesis and Characterization of New Azo Dye Complexes with Selected Metal Ions - Jarad, Amer J (Al-Nahrain Journal of Science, 2018)
Coupling reaction of 2-amino benzoic acid with phenol gave the new bidentate azo ligand. The prepared ligand was identified by Microelemental Analysis, FT-IR and UV-Vis spectroscopic technique. Treatment of the prepared ligand with the following metal ions (CoII, NiII, CuII and ZnII) in aqueous ethanol with a 1:2 M:L ratio and at optimum pH, yielded a series of neutral complexes of the general formula [M(L)2]. The prepared complexes were characterized using flame atomic absorption, (C.H.N) Analysis, FT-IR and UV-Vis spectroscopic methods as well as magnetic susceptibility and conductivity measurements. The nature of the complexes formed were studied following the mole ratio and continuous variation methods, Beer’s law obeyed over a concentration range (1× 10-4 - 3 × 10-4 M). High molar absorbtivity of the complex solutions were observed. The stability constant of the complexes have also been studied. Azo-dyes, azo-aromatic ligand, synthesis, azo complexes